The slow ape: High infant survival and long interbirth intervals in wild orangutans. Issue 125 (December 2018) - van Noordwijk, Maria A.; Utami Atmoko, S. Suci; Knott, Cheryl D.; Kuze, Noko; Morrogh-Bernard, Helen C.; Oram, Felicity; Schuppli, Caroline; van Schaik, Carel P.; Willems, Erik P.
Abstract: Orangutans ( Pongo spp.) are reported to have extremely slow life histories, including the longest average interbirth intervals of all mammals. Such slow life history can be viable only when unavoidable mortality is kept low. Thus, orangutans' survivorship under natural conditions is expected to be extremely high. Previous estimates of orangutan life history were based on captive individuals living under very different circumstances or on small samples from wild populations. Here, we combine birth data from seven field sites, each with demographic data collection for at least 10 years (range 12–43 years) on wild orangutans to better document their life history. Using strict criteria for data inclusion, we calculated infant survival, interbirth intervals and female age at first reproduction, across species, subspecies and islands. We found an average closed interbirth interval of 7.6 years, as well as consistently very high pre-weaning survival for males and females. Female survival of 94% until age at first birth (at around age 15 years) was higher than reported for any other mammal species under natural conditions. Similarly, annual survival among parous females is very high, but longevity remains to be estimated. Current data suggest no major life history differences between Sumatran and Bornean orangutans. The high offspring survival is remarkable, noting that modern human populations seem to have reached the same level of survival only in the 20th century. The orangutans' slow life history illustrates what can be achieved if a hominoid bauplan is exposed to low unavoidable mortality. Their high survival is likely due to their arboreal and non-gregarious lifestyle, and has allowed them to maintain viable populations, despite living in low-productivity habitats. However, their slow life history also implies that orangutans are highly vulnerable to a catastrophic population crash in the face of drastic habitat change.